A unique 2D-on-3D architecture developed from ZnMn2O4 and CMK-3 with excellent performance for lithium ion batteries. (October 2017) - Zhang, Tong; Qiu, Hailong; Zhang, Min; Fang, Zhibo; Zhao, Xiaosen; Wang, Lei; Chen, Gang; Wei, Yingjin; Yue, Huijuan; Wang, Chunzhong; Zhang, Dong
Abstract: Spinel ZnMn2 O4 is considered as a potentially high-capacity anode material for Li-ion batteries. However, its low conductivity causes poor rate capability and insufficient cyclability, thus turning into a challenge for battery applications. Hybrid inorganic/ordered mesoporous carbon (CMK-3) nanostructure represents a promising material platform for next-generation energy storage due to the presence of a large surface area, which facilitates ion transport and storage, and improves electron transport. Here we report a convenient and advanced architecture design of ultrathin 2D ZnMn2 O4 nanosheets integrated on 3D CMK-3 framework. Benefiting from the sufficient electrochemically available interfaces and abundant electronic/ionic pathways provided by the ultrathin ZnMn2 O4 and the interconnected channels of CMK-3 network, this ZnMn2 O4 @CMK-3 material provides a high reversible capacity of 997 mAh g −1 at 100 mA g −1 after 100 cycles, a strong rate capability with 693 mAh g −1 at 2 A g −1, and a remarkable long-term cyclability with a capacity retention of 94% over 1600 cycles. Graphical abstract: